A three year experience in Laparoscopic Appendectomy - Wormi Sharon (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2018)
Background: Acute appendicitis is one of the most common causes of acute abdomen. It may occur from the time of infancy to old age, but the peak age of incidence is in the second and third decades of life. The lifetime risk of appendicitis is approximately 7-8%. Today in developed countries, about 8% of the population is treated for acute appendicitis in the course of their lifetime. The outcome can be very serious at both extremes of life and there is a life time risk of developing acute appendicitis in about 5-8%. The aim of this study was to evaluate the clinical results of laparoscopic appendectomy (LA) for the treatment of acute appendicitis.Material and Methods: A retrospectiveanalysis fallpatients who underwent laparoscopic appendectomy diagnosed with acute appendicitis overa3-yearperiodwasreviewed. Data were retrieved from our departmental data base and analyzed using descriptive statistics. Most of the patients were diagnosed to have appendicitis by ultrasound or have ruled out other cause of right lower abdominal pain especially in females.Results: Out of the 226 patients who underwent laparoscopic appendectomy, 138(61.1%) were females and the remaining 88(38.9%) were males. Most of them are in the age group of 21-40years. 171 (75.7%) patients were discharged within 48 hours.Conclusion: Laparoscopic appendectomy is as safe and effective as conventional surgery, has a higher diagnostic yield, causes less trauma, and offers a more rapid postoperative recovery. Such features make laparoscopy a challenging alternative to laparotomy in premenopausal women referred for urgent abdominal or pelvic surgery, or both.